2019
DOI: 10.32615/bp.2019.022
|View full text |Cite
|
Sign up to set email alerts
|

Cassava microRNAs and storage root development

Abstract: BRIEF COMMUNICATION This is an open access article distributed under the terms of the Creative Commons BY-NC-ND Licence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It has been shown that miR167 plays an important regulatory role in the morphogenesis, growth and development, and hormone secretion of plant-seed embryos [72][73][74]. Notably, miR167 was identified to be characteristically enriched during plant senescence several times by previous authors [75,76].…”
Section: Cerna Network Analysis In Response To M Glyptostroboides See...mentioning
confidence: 95%
“…It has been shown that miR167 plays an important regulatory role in the morphogenesis, growth and development, and hormone secretion of plant-seed embryos [72][73][74]. Notably, miR167 was identified to be characteristically enriched during plant senescence several times by previous authors [75,76].…”
Section: Cerna Network Analysis In Response To M Glyptostroboides See...mentioning
confidence: 95%